A molecular analysis of fushi tarazu, a gene in Drosophila melanogaster that encodes a product affecting embryonic segment number and cell fate. - Weiner, A.J.; Scott, M.P.; Kaufman, T.C. (Cell, 1984)
Mutations at the fushi tarazu locus in Drosophila melanogaster affect both segment number and the pattern of cuticular structures on alternating segments of embryos. The ftz gene has been cloned and characterized. Two mutations, ftzw20 and ftzRpl are associated with lesions in a 3.2 kb fragment of DNA cloned in the Antennepedia Complex (ANT-C) chromosome "walk." The structure of DNA isolated from the ftzw20 and ftzRpl chromosomes indicates that the mutations are associated with a 4.9 kb insertion of DNA and a chromosomal rearrangement breakpoint, respectively. The 3.2 kb genomic DNA fragment hybridizes to a 1.8 kb polyadenylated transcript which accumulates maximally at 2-4 hr of embryonic development. The ftzw20 and ftzRpl mutations have different phenotypic consequences for the developing embryo, although both mutations interrupt the 1.8 kb transcription unit. The genetic and molecular data indicate that the 1.8 kb transcript derives from the ftz locus. The gene products are synthesized and utilized several hours prior to the visibly detectable morphogenetic events which the gene apparently regulates.